Co-designing User Experience of Moodle Workspaces in Higher Education - Process and Principles - Havinen, Laura; Mäkipää, Juho-Pekka; Rousi, Rebekah (Springer, 2025)
Studies have shown that user experience (UX) in course learning platforms impacts learning. UX not only stems from user interface design, but the design of instructional information within the workspace. This study examines the teacher-led design elements that students experience to improve the UX of Moodle workspaces. During the study, students were asked to re-design their course workspace for better UX. The study was implemented in two UX courses in 2021 (N = 35) and 2024 (N = 31). Through co-design workshops, students identified problematic object-level UX issues in the workspaces. We conducted a content analysis on student reports to identify themes describing the issues. From these themes, we derived design principles to improve UX in the Moodle workspace. The results indicate connections between practical improvements and the intended UX in the context of course workspaces. In addition, the study demonstrates how co-design can be used to improve the UX of a course workspace.
Keywords: design; co-design; user experience; learning platforms; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Viestintätieteet|en=Communication Studies|